PERSEPSI REMAJA TERHADAP PERFNIKAHAN DINI DI DESA TANJUNG SARI KECAMATAN KUALA CENAKU KABUPATEN INDRAGIRI HULU - Ika Safarida; Titi Maemunaty; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine adolescent perceptions of early marriage in Tanjung Sari Village, Kuala Cenaku District, Indragiri Hulu Regency. The population in this study were 50 adolescents. So the sample of this study was 44 people and 20 adolescents who were taken from Penyasawan Village, Kampar District, Kampar Regency for the trial sample with a critical level of 5%, the sample used was simple random sampling. The data collection instrument was a questionnaire with 40 statements and after the trial there were only 37 valid statements to be used as a research instrument. From the research findings on the four indicators, it can be concluded that these indicators are classified as good. This is evidenced by the presentation of recapitulation of adolescent perceptions of early marriage in Tanjung Sari Village, Kuala Cenaku District, Indragiri Hulu Regency, indicators; (1) physical and psychological aspects with a mean value of 4.42 and a standard deviation of 0.63 which is classified as high, (2) the economic aspects of the mean value of 4.52 and standard deviation of 0.58, and (3) social aspects of the value of Mean 4 , 45 and Standard Deviation 0.60, (4) aspects of education with a mean value of 4.46 and a standard deviation of 0.64. Youth perceptions of early marriage in Tanjung Sari Village, Kuala Cenaku District, Indragiri Hulu Regency are high. This means that adolescents have a good understanding of early marriage.Key Words : Perception, Early Marriage, Youth